Evaluasi Aktivitas Antimikroba (Streptococcus agalactiae) Menggunakan Exstrak Buah Mahkota Buah (Phaleria macrocarpa L.) dengan Pelarut yang Berbeda (Jurnal Ilmu dan Teknologi Hasil Ternak, 2017)
This research was aimed to determine the antibacterial activity of mahkota dewa extract and the effective concentration of mahkota dewa extract against Streptococcus agalactiae. This research was conducted from 2Mayth to 2Juneth 2016. The material ware Streptococcus agalactiae bacteria which isolated from mastitis milk, mahkota dewa which extracted using Aquades and ethanol. The method design was experiment research using Nested Design with 6 treatments and 5 replications. The concentrations of the treatments were P1 (10%), P2 (20%), P3 (30%), P4 (40%) and P5 (50%) and positive control P0 (iodips 10%). The collected data were analyzed using the analysis of variance indicated the significant effects, the least significant different test (LSD) was then employed. Mahkota dewa extract using ethanol (50%) result showed that significantly (P<0.01) on growth of Streptococcus agalactiae was 20.34Â± 0.92mm. Mahkota dewa extract using aquades (50%) result showed that significantly (P<0.01) on growth of Streptococcus agalactiae was 10.0 Â± 0.50 mm. The conclusion of this research is Mahkota dewa fruits extract with ethanol had inhibitory higher in habiting the Streptococcus agalactiae bacteria compared to aquades solvent. The best of treatment of Mahkota dewa fruits extract with ethanol and Aquades solvent in concentration 50% had a high ability to inhibit the growth of Streptococcus agalactiae.